USE OF INTERACTIVE METHODS TRAINING IN PREPARING FUTURE TEACHERS FOR PEDAGOGICAL INTERACTION WITH STUDENTS - O. Lavrentyeva (Academy of Cognitive and Natural Sciences, 2022)
In article the approaches to students' preparing to the pedagogical co-operation with pupils have been considered. The effectiveness of using interactive methods and ways of professionally significant features of future teachers forming process.